1997
DOI: 10.1351/pac199769010091
|View full text |Cite
|
Sign up to set email alerts
|

Localized triplet diradicals as a probe for electronic substituent effects in benzyl-type radicals: The ΔD scale

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…The large D value suggests that the triplet state is not derived from the 1,3‐diradical moiety but from a benzene moiety. The typical D value for triplet 1,3‐diphenylpropane‐1,3‐diyl diradical species is known to be about 0.05 cm −1 ; D values of about 0.12–0.15 cm −1 have been reported for the triplet state of benzene derivatives such as benzene itself and 1,3‐dicyanobenzene . Disappearance of the typical triplet signals under dark conditions indicated that they were derived from the 470 nm species.…”
Section: Resultsmentioning
confidence: 99%
“…The large D value suggests that the triplet state is not derived from the 1,3‐diradical moiety but from a benzene moiety. The typical D value for triplet 1,3‐diphenylpropane‐1,3‐diyl diradical species is known to be about 0.05 cm −1 ; D values of about 0.12–0.15 cm −1 have been reported for the triplet state of benzene derivatives such as benzene itself and 1,3‐dicyanobenzene . Disappearance of the typical triplet signals under dark conditions indicated that they were derived from the 470 nm species.…”
Section: Resultsmentioning
confidence: 99%
“…The traditional approach relies on the concept of ‘atomic spin densities’ and a simple point dipole model of spin–spin interactions. In ‘localized’ diradicals (such as cyclopentane‐1,3‐diyls), the D parameter decreases with the third power of the distance d AB between the ‘radical sites’ A and B and is proportional to the spin densities ρ at both centers (Eqn (2)): D~ρAρB/dAB3…”
Section: Resultsmentioning
confidence: 99%
“…This relationship has been firmly established by elegant EPR studies on various diradicals by Adam and coworkers and it has been used to study substituent effects on the spin density distribution within these systems . It relies on the assumption that spin‐orbit contributions to the ZFS can be completely neglected (which is usually justified for hydrocarbon systems) and that the spin–spin interactions can be treated within a simple point dipole scheme.…”
Section: Resultsmentioning
confidence: 99%
“…In the last decade, the isolation of persistent singlet and triplet 1,3‐diphenylpropane‐1,3‐diyl diradicals, DR , has been developed by using appropriate molecular designs and low‐temperature matrix‐isolation techniques in the photochemical denitrogenation of 2,3‐diazabicyclo[2.2.1]heptane derivatives, AZ (Scheme b) . Herein, the emission spectroscopic analyses of the 1,2‐diarylcyclopropane derivatives CP1 a (Ar=Ph, X=OMe), CP1 b (Ar=Ph, X=Me), CP2 a (Ar=2‐Naph, X=OMe), and CP2 b (Ar=2‐Naph, X=Me) were investigated under low‐temperature glassy matrix conditions.…”
Section: Methodsmentioning
confidence: 99%
“…As was mentioned above, the 1,2‐diphenylcyclopropanes with X=Me ( CP1 b and CP2 b ) did not show any long‐wavelength emission over 450 nm. To obtain more insight into the emission phenomena, the matrix isolation of T‐ DR1 b (Ar=Ph, X=Me) and its emission analysis were conducted at 77 K in 3MeP (Figure F). First, the triplet diradical T‐ DR1 b was generated using photochemical denitrogenation of AZ1 b ( λ max ≈365 nm, 1.0×10 −3 m ) at 77 K in a sealed 3MeP solution under degassed conditions.…”
Section: Methodsmentioning
confidence: 99%